Penyuluhan Fisioterapi Mengenai Nyeri Punggung Bawah Pada Lansia di Puskesmas Kendalsari Kota Malang - Seizila Neya Yasyfa; Safun Rahmanto; Bonita Suharto (Rena Cipta Mandiri, 2025)
Low back pain is defined as pain in the lower back area, which can be local, radicular or both and localized between the lower costal arches, especially the lumbosacral region and accompanied by pain radiating to the legs and feet. The main factor causing low back pain is ergonomic problems. In addition, work that involves excessive repetitive movements, improper body position. The method used is health promotion by providing counseling and education about low back pain and physiotherapy management in the form of stretching that can be done independently. The media used is a leaflet. The purpose of the counseling is to provide education and physiotherapy treatment and increase knowledge related to low back pain in the elderly at the Kendalsari Health Center, Malang City. Based on the evaluation results, there was an increase in knowledge and understanding of low back pain to prevent and reduce low back pain.